Sosialisasi Penggunaan APD Terhadap Nelayan Tradisional - Adelina Fitry R Lubis; Adinda Adinda; Rahmi Indah Syahrina Nasution (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Fishermen are a group of people whose livelihoods depend on marine products for catching and cultivating fish. Most fishermen live on the coast, close to their place of work. This research uses a literature review methodology that focuses on variables or topics studied from previous research. The act of literature review involves collecting data from libraries and documentation. Data related to the socialization of the use of PPE by traditional fishermen was obtained from research articles and literature reviews. By using predetermined inclusion criteria, namely complete scientific publications published in the last five years, the procedure for collecting articles is carried out by searching literature sources. Review literature sources can be found by using the following keywords in Google Scholar: Relationship between fish fishermen's complaints of dermatitis and their use of personal protective equipment in Mela II Village, Central Tapanuli Regency, North Sumatra. A device called personal protective equipment (PPE) is used to shield the body or oneself from the risks associated with workplace accidents. PPE can lessen the severity of work accidents, notwithstanding its shortcomings.